Formulating The Concept Of Progressive Judge In Handling Corruption Cases In Indonesia - Syamsudin, M. (Universitas Islam Indonesia, 2021)
The main problem studied in this writing is the failure of judges to eradicate corruption in Indonesia in their decisions. The data is collected by interviews and studies of verdict documents. To analyze that problem there needs a study in socio-legal research with the legal hermeneutical approach. The result of this research shows the weaknesses of judges in deciding verdicts for corruption. The narrow interpretation of corruption and the performance orientation of judges contributed to the failure of judges in eradicating corruption. There needs to be an introduction of the concept progressive judges to overcome the aforementioned problems. Progressive Judges are judges who can creatively interpret the law on existing regulations, without having to wait for regulatory changes. Poor regulation does not have to be a barrier for progressive judges to present fair, definite, and useful laws because they can make progressive interpretations of existing regulations.Keywords: The concept of progressive judges; eradicate corruptions; the legal hermeneutic approachPerumusan Konsep Hakim Progresif Dalam Penanganan Kasus Korupsi Di IndonesiaAbstrakMasalah utama yang dikaji dalam penulisan ini adalah kegagalan hakim dalam memberantas korupsi di Indonesia dalam putusannya. Pengumpulan data dilakukan dengan wawancara dan studi dokumen putusan. Untuk menganalisis permasalahan tersebut perlu adanya kajian dalam penelitian sosio-legal dengan pendekatan hermeneutika hukum. Hasil penelitian ini menunjukkan kelemahan hakim dalam memutus perkara korupsi. Penafsiran korupsi yang sempit dan orientasi kinerja hakim berkontribusi pada kegagalan hakim dalam memberantas korupsi. Perlu adanya pengenalan konsep hakim progresif untuk mengatasi permasalahan tersebut di atas. Hakim Progresif adalah hakim yang secara kreatif dapat menafsirkan undang-undang pada peraturan yang ada, tanpa harus menunggu perubahan peraturan. Regulasi yang buruk tidak harus menjadi penghalang bagi hakim progresif untuk menghadirkan hukum yang adil, pasti, dan bermanfaat karena mereka dapat membuat interpretasi progresif terhadap peraturan yang ada.Kata kunci: Konsep hakim progresif; memberantas korupsi; pendekatan hermeneutika hukum